Construcția unei teorii a drepturilor omului: între rațiune și lege [Articol] - Ciobanu, Rodica (Tipografia Artpoligraf, 2020)
The article discusses the issue of human rights from the perspective of the theoretical analysis´ trends and the problems registered in the area of the protection of human rights nowadays. The main argument is based on the fact that the debates on human rights are open as a result of some new situations that appear in people’s lives, of the diversification of needs, of the claims for new demands, and of new rights. We conclude, once again, that the individuals' need to have their rights respected relates directly to the institutions’ activity, which should encourage their feeling of security and self-value.
THE DEVELOPMENT OF A THEORY OF HUMAN RIGHTS: BETWEEN REASON AND LAW
Keywords: human rights; democratization; humanism